Análise espacial dos acidentes de trabalho registrados no sistema de informação de agravos de notificação (SINAN) em uma capital brasileira - Katia Rita Gonçalves (2012)
Occupational accidents constitute a huge problem of public health in Brazil which is manifested by an unconcluded shared agenda of obligations aiming at a set of responsibilities for a result. When the existing Brazilian statistics concerning work-related violence, of which occupational accidents are one of the most expressive aspects, are compared, the real relevance and impact of such injuries on the profile of mortality of population nor their economic and social damages are not fairly evidenced. Its distribution occurs heterogeneously with significant concentration in the central city. Thus, getting to know their spatial behavior and their relations with the socioeconomic conditions as well as the model of development adopted in the metropolitan regions, indicated by the profile of production / consumption is fundamental for the formulation of strategies that may help the achievement of the reduction or even the elimination of those accidents. The objective of this study is to identify, describe and analyze the spatial distribution of fatal and serious occupational accidents as well as those involving children and adolescents having as reference a Brazilian city, in the period of 2007 to 2011. It is an exploratory-descriptive study of territorial basis, once it is situated in a well-defined geographical area, the city of Belo Horizonte, Minas Gerais, Brazil. Secondary data available in the Municipal Health Secretariat of Belo Horizonte were used as guidance. The data concerning serious occupational accidents of derive from SINAN. The Annual Relation of Social Information and data from Brazilian Institute of Geography and Statistics were also used. For the geo-processing, generation of maps, the Software MapInfo Professional (GEOGRAPH) and cartography bases from IBGE were the chosen material. There was also online based bibliographic research. The data reveals a continuous growing in the indicators of morbidity and mortality of serious occupational accidents, which are concentrated in the age between 18 and 39 years of age. Most data show a predominance of male workers who are inserted in the formal market (the number of accidents involving informal workers is unknown, since there is a massive amount of cases that are not registered), live in the urban zone and have in average eight years of permanence in school. They are also involved in the highest number of cases of temporary incapacity, being most of the cases registered either in the companys installations or in public highways. The productive segments with the highest concentration of cases are the building industry, market, provision of services, management activities and complementary services and industry of transformation. The causes of accidents are concentrated in the chapter of CID 10 which concerns other external causes of accidental traumatisms emphasizing the categories W01 to W29. The most expressive injuries regarding the CID 10 code are the traumatisms of wrist and hand. In what regards occupation, the activities related to groups of building workers are in emphasis. A reduction of fatal occupational accidents could be noticed in this study. The accidents were geo-referenced to their respective Sanitary District. The spatial analyses identified the urban nature of most serious occupational accidents in the city of Belo Horizonte. The use of spatial analyses enables the monitoring of occupational accidents and helps the spreading of information, contributing for Health Vigilance Situation.